De colônia africana a bairro Rio Branco : desterritorialização e exílio social na terra do latifúndio : Porto Alegre, 1920-1950 - Silveira , Alexandre Barcelos (2015)
It existed in the late nineteenth and mid-twentieth territory in Porto Alegre that it has received a large number of former prisoners after the end of slavery. In it, family ties were strengthened. Traditions, religion and culture were cultivated at the time immigration was coming, and the rest of Brazil. This territory was named African colony. This paper delves into the period between 1920 and 1950 to investigate, from the point of view of the narratives of former residents of the colony, their sociability and their daily lives that often was relegated to the background by historiography. "Rebuilt" the Cologne and then we look in the archives, newspapers and relevant literature, how was the process of dispossession of poor black population to the outskirts of Porto Alegre.